EBSD Characterization of 7075 Aluminum Alloy and Its Corrosion Behaviors in SRB Marine Environment - Zhiyuan Feng; Jiao Li; Jincai Ma; Yongjin Su; Xiaoyuan Zheng; Yu Mao; Zilong Zhao (Journal of Marine Science and Engineering, 2022)
Aluminum alloy 7075 is an important engineering material for ship structures. However, the corrosion of Al alloys generally exists in various environments, especially in the marine environment. Currently, the corrosion behaviors of Al alloy 7075 in sulfate-reducing bacteria (SRB) marine environment has not been well-addressed. In this paper, the corrosion effect of SRB on 7075 aluminum alloys was studied by adding SRB to real seawater. The microstructure and grain orientation of the super-hardness Al alloy 7075 were studied via the electron back-scattered diffraction (EBSD)technology, and the electrochemical impedance spectroscopy (EIS) test of the electrochemical corrosion behavior of 7075 in a variety of microorganisms, mainly SRB, in real seawater was continuously performed for 21 days. It was concluded that Al alloy 7075 has the strongest texture intensity on the (001), (111), (010), and (0–10) planes, which is 2.565. Adding SRB to real seawater accelerated the corrosion rate, and after corrosion on the 14th day, the protective film on the 7075 aluminum alloy surface was completely broken, and the impedance was significantly reduced.